Polonica concerning history and legal-political issues in the book collection of Gottfried Lengnich - Imańska, Iwona (Folia Toruniensia, 2017)
Gottfried Lengnich, a historian and lawyer who lived in Gdańsk in the 18th century left behind a collection of over 4,000 books. The collection was sold during two auctions in July and November 1774. Auction registers found in the State Library in Berlin – the Foundation of the Prussian Cultural Heritage – are available on-line. Owing to Lengnich’s academic interests, the collection includes 600 Polonicas, the majority of which are works concerning history, law and politics. The analysis of this fragment of Lengnich’s collection shows that it includes the majority of the most significant Polish and foreign authors writing about the history and law of Poland and Prussia.